2020
DOI: 10.1029/2019jc015807
|View full text |Cite
|
Sign up to set email alerts
|

Sea Ice CO2 Dynamics Across Seasons: Impact of Processes at the Interfaces

Abstract: • First long-term monitoring of both pCO2 and CO2 fluxes at sea ice interfaces in McMurdo Sound (Antarctica) from late winter to summer • Large biomass build-up is strikingly associated with transient heterotrophy and nitrate plus nitrite accumulation • New conceptual approach involving biofilm formation can explain observed inconsistencies: accumulation of nitrate plus nitrite and CaCO3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 110 publications
5
14
0
Order By: Relevance
“…With these combinations of parameters, the d 13 C value at steady state reached -10 ‰, which is a good approximation of our most enriched d 13 C signature. The occurrence of CH 4 production despite the aerobic conditions encountered in sea ice (van der Linden et al, 2020), and from a 13 C-enriched pool as suggested by the model, points toward a different pathway than the classical anaerobic ones reported in Whiticar (1999;Figure 5). Although most of the phytoplankton and microbial species involved in aerobic CH 4 production identified to date (Table 1) are not sympagic, Pseudomonas, a microbial genus that contains seawater members capable of the C-P lyase pathway, and Phaeocystis spp.…”
Section: Contribution From a Hydrothermal Sourcementioning
confidence: 67%
See 2 more Smart Citations
“…With these combinations of parameters, the d 13 C value at steady state reached -10 ‰, which is a good approximation of our most enriched d 13 C signature. The occurrence of CH 4 production despite the aerobic conditions encountered in sea ice (van der Linden et al, 2020), and from a 13 C-enriched pool as suggested by the model, points toward a different pathway than the classical anaerobic ones reported in Whiticar (1999;Figure 5). Although most of the phytoplankton and microbial species involved in aerobic CH 4 production identified to date (Table 1) are not sympagic, Pseudomonas, a microbial genus that contains seawater members capable of the C-P lyase pathway, and Phaeocystis spp.…”
Section: Contribution From a Hydrothermal Sourcementioning
confidence: 67%
“…CH 4 produced from bacterial degradation of methyl phosphonate (MPn) esters, which are part of the semilabile dissolved organic matter (DOM) pool, is characterized by a d 13 C of -39 ‰ (Repeta et al, 2016). DOM was not measured in these ice cores but can be approximated by the POC concentrations (Figure 12) reported in Van der Linden et al (2020). The vertical profiles of POC reach 2,890 mM at the ice bottom but show little variation in the ice interior, with concentrations lower than 35 mM, except for 2 local peaks, on September 19 at 103.5-cm depth (165 mM) and on October 18 at 47-cm depth (343 mM).…”
Section: Contribution From a Hydrothermal Sourcementioning
confidence: 91%
See 1 more Smart Citation
“…The ice platelets can eventually be incorporated onto the base of the ice shelf (marine ice) via buoyant accumulation (Oerter et al., 1992), or be carried out from the ice shelf cavity and deposited beneath neighboring sea ice (subice platelet layers; Langhorne et al., 2015; Tison et al., 1998). Under sea ice, in‐situ growth can continue, creating a porous and friable subice platelet layer from which the highest concentrations of sea‐ice algae (up to 374 mg C L −1 and 6.5 mg Chl a L −1 ) have been reported (Arrigo et al., 2010; Bombosch, 2013; Smetacek et al., 1992; van der Linden et al., 2020). The origin of marine ice Fe is often associated with highly reactive glacial flour produced from subglacial physical and chemical weathering (Wadham et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting chemical activity of these impurities within sea ice influences the exchange of greenhouse gases (GHGs), including carbon dioxide (CO 2 ), methane (CH 4 ), and N 2 O (notable GHGs), across the ocean-sea ice-atmosphere interface (Lannuzel et al, 2020). During winter, sea ice acts as a source of CO 2 with high brine partial pressure of CO 2 due to increased brine concentrations and associated ikaite precipitation (Rysgaard et al, 2011;Geilfus et al, 2013;Fransson et al, 2015;Geilfus et al, 2016), whereas in spring and summer, sea ice shifts to become a sink for atmospheric CO 2 due to brine freshening, ikaite dissolution, and the biological carbon pump (Rysgaard et al, 2011;Geilfus et al, 2012;Van der Linden et al, 2020).…”
Section: Introductionmentioning
confidence: 99%